2020
DOI: 10.1155/2020/1404915
|View full text |Cite
|
Sign up to set email alerts
|

The Recombinant Protein EphB4-Fc Changes the Ti Particle-Mediated Imbalance of OPG/RANKL via EphrinB2/EphB4 Signaling Pathway and Inhibits the Release of Proinflammatory Factors In Vivo

Abstract: Aseptic loosening caused by wear particles is one of the common complications after total hip arthroplasty. We investigated the effect of the recombinant protein ephB4-Fc (erythropoietin-producing human hepatocellular receptor 4) on wear particle-mediated inflammatory response. In vitro, ephrinB2 expression was analyzed using siRNA-NFATc1 (nuclear factor of activated T-cells 1) and siRNA-c-Fos. Additionally, we used Tartrate-resistant acid phosphatase (TRAP) staining, bone pit resorption, Enzyme-linked immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
1
4
2
Order By: Relevance
“…This suggests that the differentiation and maturation of osteoclasts require the interaction of osteoblasts. However, the result is in contradiction with the finding that EphB4 could inhibits osteoclast differentiation as a reverse signal (Ge et al, 2020). Thus, we speculate that this effect may be through other signaling pathways; for example, the RANKL/OPG pathway of osteoblasts may be increased by LIPUS.…”
Section: Discussioncontrasting
confidence: 90%
“…This suggests that the differentiation and maturation of osteoclasts require the interaction of osteoblasts. However, the result is in contradiction with the finding that EphB4 could inhibits osteoclast differentiation as a reverse signal (Ge et al, 2020). Thus, we speculate that this effect may be through other signaling pathways; for example, the RANKL/OPG pathway of osteoblasts may be increased by LIPUS.…”
Section: Discussioncontrasting
confidence: 90%
“…Therefore, further studies are needed to investigate the role of Jmjd3 in RANKL expression. Our results and previous studies have shown that RANKL expression increases when the expression of EphB4 decreases (Ge et al, 2020). After overexpressing EphB4 in Jmjd3‐silenced osteoblasts, the formation of osteoclasts and the expression of NFATc1, c‐Fos, TRAP and cathepsin K in RAW264.7 cells was significantly inhibited when co‐cultured with the supernatant of these cells.…”
Section: Discussionsupporting
confidence: 86%
“…The binding of EphB4 on the membrane of osteoblasts to EphrinB2 on the membrane of osteoclasts activates downstream signalling pathways and suppresses osteoclastogenesis, a process referred to as a ‘reverse signal’. Conversely, when EphrinB2 binds to EphB4 on the osteoblast membrane, the binding promotes the mineralization of osteoblasts, which is known as a ‘forward signal’ (Ge et al, 2020; Mundy & Elefteriou, 2006; Zhao et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of EphB4 led to the inhibition of both p-ERK and p-STAT1, but the ultimate effect on tube formation is reduction. A previous study showed that EphB4 relieved the release of proinflammatory factors [32]. In our study, the knockdown of EphB4 showed a tendency to increase inflammation-related factors, such as IL-6, but did not bring a significant difference.…”
Section: Discussioncontrasting
confidence: 46%